Baseline presentation of atypical anorexia nervosa in Singaporean adolescents: a retrospective cohort study - Chu Shan Elaine Chew; E. Eric Tay; Mei En Hannah Marian Lie; Khairunisa Binte Khaider; Courtney Davis (Journal of Eating Disorders, 2023)
Abstract Background While atypical anorexia nervosa (AAN) has been found to present with significant physical and psychological complications, the presentation of AAN has not been described in a multi-ethnic Singaporean population. Methods This retrospective cohort analysis aimed to characterize the baseline presentation of adolescents with anorexia nervosa (AN) (N = 317) and AAN (N = 141) in a Singaporean cohort that presented to a specialist paediatric eating disorder program between January 2010 and October 2020 for assessment. Results In patients with AAN, there were increased proportions of males (16% vs. 7%) and of Malay ethnicity (11% vs. 4%) compared to AN. Compared to adolescents with AN, adolescents with AAN had lower rates of admission (61% vs. 81%), bradycardia (45% vs. 75%), and hypotension (7% vs. 21%) but had a higher rate of syncope (13% vs. 7%). Likewise, adolescents with AAN had higher rates of self-harm and drug overdose (14% vs. 1.5%) requiring admission, more purging (45.1% vs. 14.8%) and more shape concerns. Conclusion Highlighting the severity of the illness, Singaporean adolescents with AAN presented with physical complications of malnutrition and had more severe eating disorder psychopathology and a higher frequency of other psychological comorbidities than did adolescents with AN.